COMMONLY USED RAW FRUIT AND VEGETABLE JUICES OVERALL ANTIOXIDANT ACTIVITY DETERMINATION BY MEANS OF BRIGGS-RAUSCHER REACTION - MUNTEAN, Norbert; SZABÓ, Gabriella (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The antioxidant capacity of commonly used raw fruit and vegetable juices was determined by means of the Briggs-Rauscher oscillating system in batch conditions. Though it is very important to know the composition of a juice mixture, sometimes it is not enough to predict the behavior, because of the interaction of the different components. Antioxidant mixtures can present discrepancy in their activity compared to the individual values of the different components. Inhibition times at different concentrations were determined for a number of juices; they presented a linear dependence vs. their concentration. The relative antioxidant activity of a mixture of juices was measured and compared to that of the individual juices and a synergistic effect was found.